Gentrification, Social Justice and Personal Ethics. (7th May 2016) - Marcuse, Peter
Abstract: Gentrification, leading to displacement, is an increasingly recognized social problem. Individuals who are confronted with tight housing possibilities but have adequate incomes confront personal ethical issues on whether to act in ways that may contribute to displacement of lower‐income residents, and researchers working on housing issues may be particularly concerned. In order to work out an ethical position, clarity is first needed on the differences among the various aspects of gentrification. The working definition used here is that gentrification includes the danger of displacement. A public policy response is thus required to deal with its social injustices. Specific steps are suggested for the development of such policy. Secondly, the suggestion is made that the individual choice of whether to move in or not is, importantly, a personal ethical choice and should take into account both the economic and political impact of the move itself but also the contribution that can be made through collective and political action by an in‐mover to deal with the injustices of gentrification. However, it is also an ethical choice for the professions involved and their associations.